Measuring The Efficiency of Madrasah Aliyah Negeri in Bangka Belitung Province Through Data Emvelopment Analysis (DEA) - Dinar Pratama (STAI Hubbulwathan Duri, 2022)
The importance of measuring the efficiency of State Madrasah Aliyah in the Province of the Bangka Belitung is at least based on the low achievement of Madrasah output or National Examination scores. This shows that the implementation of Madrasah Aliyah in terms of input and output is still not efficient. This study aims to measure the efficiency of State Madrasah Aliyah in the Province of the Bangka Belitung Islands in the 2017/2018 and 2018/2020 academic years. This research uses a Data Development Analysis (DEA) approach and is a type of qualitative research with non-parametric statistical analysis. The results of the DEA analysis show that there are inefficient DMUs in the 2017/2018 – 2018/2019 academic year, namely, MAN 1 Bangka, MAN 1 Belitung, and MAN 1 Pangkalpinang. meanwhile, MAN 1 West Bangka and MAN IC Bangka Tengah are DMUs that have been consistently efficient in the 2017/2018 - 2018/2019 Academic Year. Several corrective steps can be taken by the inefficient DMU, such as, 1) reducing the amount of budget that is adjusted to the ideal number of students by 236, 2) DMU needs to build a strict student selection system to maintain the ideal number of students, 3) increase the quantity and quality of teachers who have been certified, and 4) maintain a teacher-to-student ratio of at least 1:16.